Faktor-Faktor Yang Berhubungan Dengan Kejadian Stroke Pada Usia Produktif - Martono Martono; Rendi Editya Darmawan; Devita Nur Anggraeni (Jurnal Keperawatan Muhammadiyah, 2022)
Stroke is the most common health problem globally. According to the results of Basic Health Research (Riskesdas) in Indonesia in 2013, and 2018 showed an increase in prevalence of 7 per mile (per 1000 population) in 2013, and 10.9 per mile (per 1000 population) in 2018. According to Riskesda in 2018, as many as 52.3 per mile (per 1000 population) stroke cases are of productive age with an age range of 15 to 64 years which can cause temporary or permanent cessation so as to reduce work productivity and increase disease cases. To determine the factors associated with the risk of stroke in productive age. This study aims to determine the factors associated with the risk of stroke in productive age. This type of research is descriptive correlation with logistic regression test as many as 112 respondents (total sampling) according to the inclusion and exclusion criteria by analyzing the RM sheet at the Setabelan Health Center Surakarta City. Factors associated with the incidence of stroke is hypertension (contribution 21.1%) while age, gender, diabetes mellitus, hypercholesterolemia, and obesity do not have a significant relationship with the incidence of stroke. The most dominant factor with the incidence of stroke is hypertension. Based on the research, it can be said that of the 6 variables there is 1 variable that has an effect, namely hypertension so that the most dominant factor is hypertension.